1969
DOI: 10.1002/ijc.2910040414
|View full text |Cite
|
Sign up to set email alerts
|

Some factors affecting carbohydrate metabolism in hepatic tissues of different growth rates

Abstract: Aspects of carbohydrate metabolism, namely glycogen concetttration, glucokinase activity, hexokinase activity, lactate and a-glycerophosphate production, were compared with growth rate in regenerating liver and two transplantable hepatomas (5123-0 and 7777). Lactate production with glucose as substrate was greater with whole homogenates than with supernatant fractions for the hepatomas but the reverse was the case with control, sham-operated and regenerating liver. Nicotinamide had a greater effect on lactate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1972
1972
2001
2001

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A short review of reported changes in glucose metabolism in response to hydroxyurea treatment (a potent DNA/RNA synthesis inhibitor also used to treat CML) is given here to address whether decreased glucose uptake, activation, and oxidation are unique to direct targeting of the kinase activity of Bcr-Abl by STI571. Glucokinase activity of regenerating liver showed a dose-dependent increase (24 h) or no change (48 and 96 h) after 250 and 1000 mg/kg hydroxyurea treatment in rats (26). In the same study, hexokinase activity was decreased after 250 mg/kg hydroxyurea treatment but increased after 1000 mg/kg hydroxyurea treatment in hepatoma 7777 and 3924-A cells.…”
Section: Discussionmentioning
confidence: 70%
“…A short review of reported changes in glucose metabolism in response to hydroxyurea treatment (a potent DNA/RNA synthesis inhibitor also used to treat CML) is given here to address whether decreased glucose uptake, activation, and oxidation are unique to direct targeting of the kinase activity of Bcr-Abl by STI571. Glucokinase activity of regenerating liver showed a dose-dependent increase (24 h) or no change (48 and 96 h) after 250 and 1000 mg/kg hydroxyurea treatment in rats (26). In the same study, hexokinase activity was decreased after 250 mg/kg hydroxyurea treatment but increased after 1000 mg/kg hydroxyurea treatment in hepatoma 7777 and 3924-A cells.…”
Section: Discussionmentioning
confidence: 70%
“…Their effects are not restricted to this enzyme; they also inhibit NAD glycohydrolase (Masmoudi and Mandel, 1987). By inhibiting NAD glycohydrolase, they may affect some events of cellular metabolism (Lea et al, 1969). ATP was shown to be more effective in inhibiting NAD glycohydrolase in nonsynaptic mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Itis more likely that the lowered content of UDPIglucose is caused by a decreased rate of synthesis. It is known tha-t the hexokinase activity increases (Lea et al, 1970) and phosphoglucomutase activity remains constant (Weber & Cantero, 1957) after partial hepatectomy. Moreover, the coenzyme UTP, necessary for the synthesis of UDP-glucose, increases by 50 % within 3 h after partial hepatectomy (Bucher & Swaffield, 1969).…”
Section: Discussionmentioning
confidence: 99%